The phenomenon of substitution in the sound of the hamza in the dialect of the Emirate of Sharjah - Al-Yasi, Aisha; Alfuqara , SaifAldaen (Al-Adab Journal, 2025)
Arabic dialects have formed a wide field of scientific studies, and although there are studies on Arabic dialects in the Arabian Gulf, some of these studies are specific to the dialect of the United Arab Emirates, but the Emirate of Sharjah has its own dialect character that the linguist notices when dealing with its people.This study aims to highlight some aspects of the dialect of the Emirate of Sharjah. By addressing the issue of phonetic changes in the hamza sound, which has witnessed major historical and technological changes over time. It also seeks to link this dialect to the Arabic dialect system by monitoring the dialect remnants of ancient Arabic dialects in it.The importance of the study stems from the fact that it addresses a linguistic topic in linguistics, which is living dialects, in addition to the lack of studies on the dialect of the Emirate of Sharjah.The study followed the descriptive and analytical approach by observing, classifying, and phonologically analyzing vocal phenomena to show the manifestations of the vocal changes in the sound of the hamza and explaining them according to phonetic laws. It also benefited from data from field linguistics through narration and monitoring the speech of the language’s people to reveal dialect differences.The study showed that the Sharjah dialect has phonetic issues, especially the hamza sound, which constitute an extension of phonetic developments in Arabic dialects, and that some of it represents dialect deposits from ancient dialects.